Saving Hasankeyf: Limits and Possibilities of International Human Rights Law. Issue 1 (19th March 2018) - Aykan, Bahar
Abstract: This article explores the limits and possibilities of international human rights law in protecting cultural heritage from state-led destruction. It does so by focusing on two attempts by activists and non-governmental organizations to have the United Nations and the Council of Europe intervene to save the ancient city of Hasankeyf in Turkey's southeast region, which will soon be flooded by the reservoir waters of the Ilısu Dam. Adopting a heritage rights focus, these grassroots initiatives have argued that Hasankeyf's destruction would constitute a violation of human rights because it would deprive people of their right to participate in, and benefit from, cultural heritage. I suggest that, as powerful attempts to link cultural heritage and human rights, these cases demonstrate the need for more effective and legally binding international frameworks to protect heritage rights as an aspect of human rights.